STRATEGIZING THE DEVELOPMENT OF MSME IN DISTRICT X - Sari, Nila (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Micro, Small and Medium Enterprises (MSMEs) is a business segment that has the potential to grow and become one of the backbones of economic development in Indonesia, one of which is in Regency X. In order to support the achievement of the vision and mission of Regency X, the government of Regency X intends to spur the development of MSMEs in its region by providing an MSME development program that aims to help MSMEs to develop into one of the pillars of regional economic development in Regency X by encouraging tourism development and encouraging the development of the creative economy (startup). This study uses quantitative and qualitative approaches. The quantitative approach was carried out to obtain influential criteria for the development of MSMEs in Regency X which were then analyzed by the Cochran Q Test, the results of the selected criteria were continued with the calculation of the weights of internal factors and external factors, the calculation of the Internal Strategic Factors Analysis Summary (IFAS) and External Strategic Factors Analysis Summary (EFAS) matrices, determination of the SWOT analysis cartesian diagram and SWOT matrix. A qualitative approach was used to explore information on internal and external factors affecting the development of MSMEs in Kabupaten X and determine MSME development strategies based on the IFAS and EFAS matrices from the SWOT analysis results.